Electrical Control of Magnetic Order Transition in 2D Antiferromagnetic Semiconductor FePS3 - Mengjuan Mi; Qing Zhang; Shilei Wang; Xiandong Zhang; Han Xiao; Lixuan Yu; Houning Song; Chao Ma; Shuang Dai; Bingbing lyu; Jiyu Fan; Bing Shen; et al. (Advanced Science)
Abstract Manipulating the magnetic order transition of 2D magnetic materials is an important way for the application of spintronic devices, and carrier concentration modulation is a commonly used effective regulation method. Here the magnetic ground state of FePS3 is tuned from antiferromagnetic (AFM) to ferrimagnetic (FIM) and back to AFM by electron doping, which is achieved via the intercalation of various organic cations. The doped FePS3 with FIM order exhibits a Curie temperature Tc of ≈110 K, a strong out‐of‐plane magnetic anisotropy, and particularly an unusual hysteresis loop, where with increasing temperature, the area of magnetic hysteresis loop increases below 50 K, then decreases above 50 K and eventually disappears. Theoretical calculations indicate that at a doping concentration of 0.3–0.9 electrons per cell, spin splitting of energy bands occurs, leading to the FIM order; whereas at a doping concentration of ≥ 1.0 electrons per cell, the AFM order recovers. Such AFM‐FIM‐AFM transition is ascribed to the competition between the Stoner exchange‐dominated FM order and super‐exchange‐dominated AFM order. These results demonstrate an effective approach to engineering magnetism in 2D magnetic materials by purely electrical means for future device applications.